A Review of Poisonous Plants with Teratogenic Effects - Ayoubi, Rabia (Journal of Natural Sciences – Kabul University, 2025)
The use of medicinal plants and herbal remedies to address pregnancy-related issues is widespread among expectant mothers. However, certain plants contain bioactive compounds with teratogenic properties, which can lead to adverse outcomes such as fetal death, congenital malformations, growth retardation, and functional impairments in the fetus or newborn. These adverse effects are attributed to specific toxic constituents with teratogenic potential. This narrative review article introduces the poisonous plants with teratogenic effects and the phytochemicals responsible for their teratogenicity. This study highlights that several medicinal plants commonly employed during pregnancy possess teratogenic effects, primarily due to active compounds such as alkaloids, glycosides, terpenoids, and flavonoids. Although the teratogenicity of these plants has been demonstrated predominantly in experimental models, and in some instances further investigation is necessary for conclusive evidence, it is nevertheless advisable to avoid the use of these plants during pregnancy.